Immunomodulatory and cell cycle regulatory effects of clinacanthus nutans - Ghazali, Wan Afiqah Syahirah Wan @ Wan Azmi (2018)
This research comprises analyses of proliferative activity, nitric oxide, cytokine and phagocytosis assays to evaluate its immunomodulatory properties as well as gene expression analysis of cell cycle regulatory genes. Murine macrophage cell line (J774A.1) was treated with various concentrations (250, 125, 62.5, 31.25 and 15.625 μg/ml) of aqueous and ethanol extracts of the leaves of C. nutans. MTS assay showed enhanced cell proliferation with an EC50 range between 4.051 to 100.6 μg/ml. Cytokine assay revealed that C. nutans possesses anti-inflammatory properties and increases the nitric oxide production in macrophages with a mean of production (41-130 μmol/L) that could modulate the inflammatory response. Percentage of latex beads IgG-FITC engulfment ranged between 14.9 and 55.1%. Phagocytic activity showed increase in percentage of latex beads IgG-FITC engulfment as the concentration of the extract increased. Human gingival fibroblast cell line (HGF-1) was treated with ethanol and aqueous extracts of Clinacanthus nutans (C. nutans) leaves for 1, 3 and 7 days. Gene expression analyses showed that BCL-2 was down-regulated in ethanol extract on day 1 and 7 indicating an anti-apoptotic effect and an up-regulation on day 3 indicating its apoptotic property. Down-regulation of BAX in aqueous extract on day 1 indicated the apoptotic nature of C. nutans and up-regulation of BAX in both the extracts on all days showed its pro-apoptotic properties. Down-regulation of C-MYC in aqueous extract on day 1 could result in decrease in the number of cells due to arrest in growth. Up-regulation of C-MYC in both the extracts at all days could inhibit signals for death and survival. Up-regulation of CDK1 in the ethanol extract on day 7 and aqueous extract on day 3 and 7 showed that C. nutans could regulate cell cycle progression and promote mitosis. There was down-regulation of SUMO-1 in ethanol extract on day 1, 3 and 7 and on day 1 and 3 in aqueous extract which results in the failure of SUMO-1 to conjugate to cellular proteins. There was up-regulation of SUMO-1 in aqueous extract on day 1, 3 and 7 and on day 1 and 3 in ethanol extract. The results of this study support the role of C. nutans extracts in regulating cellular processes such as apoptosis, protein stability, transcription and nuclear transport by modulating the gene expression of BCL-2, BAX, C-MYC, CDK1 and SUMO-1 thereby regulating cell cycle activity.